AB0378 UPGRADING THERAPY STRATEGY IMPROVES PREGNANCY OUTCOME IN ANTIPHOSPHOLIPID SYNDROME: A COHORT MANAGEMENT STUDY. (2nd June 2020) - Hoxha, A.; Favaro, M.; Calligaro, A.; Del Ross, T.; Ruffatti, A. T.; Infantolino, C.; Tonello, M.; Mattia, E.; Ruffatti, A.
Abstract : Background: While it is generally agreed that pregnant APS patients should receive personalized treatment, evidence-based guidelines for these patients continue to be lacking. Objectives: The current study was designed as a management cohort study aiming to evaluate the efficacy and safety of different treatment strategies for pregnant APS patients in the attempt to provide some practical suggestions for attending physicians. Methods: One-hundred-twenty-seven consecutive pregnancies were assessed; 87 (68.5%) with a history of pregnancy morbidity alone were treated with prophylactic low molecular weight heparin (LMWH)+low-dose aspirin (LDA, 100 mg) [Group I] and 40 (31.5%) with a history of thrombosis and/or severe pregnancy complications with therapeutic LMWH+LDA [Group II]. LMWH doses were increased throughout the pregnancies depending on the patients' weight gain, and treatment was switched to a more intensive one at the first sign of maternal/fetal complications. The study's primary outcome was live births. Results: There were no significant differences in live birth rate between Group I (95.4%) and Group II (87.5%). Even, fetal complication rate was similar in the two groups; the Group II nevertheless had a higher prevalence of maternal and neonatal complications (p=0.0005 and p=0.01, respectively) and registered a significantly lower gestational age at delivery and birth weight (p=0.0001 and p=0.0005, respectively). Two patients in Group I switched to Group II therapy, six patients in Group II switched to a more intensive treatment strategy (weekly plasma exchange+ fortnightly intravenous immunoglobulins in addition to therapeutic LMWH+LDA). Comparison of the clinical and laboratory characteristics between patients who had shifted to a more intensive therapy and those who did not showed a significant prevalence of history of thrombosis ± pregnancy morbidity (p=0.02, OR 5.96, 95% CI 1.33-26.62) previous pregnancy complications (p=0.02, OR 8.32, 95% CI 1.67-41.3), triple aPL positivity (p <0.0001, OR 97.13, 95% CI 10.6-890) and pregnancy complications (p<0.0001, OR 197, 7, 95% CI 10.57-3699) in upgrading group, instead single aPL positivity significantly prevailed (p=0.003, OR 0.06, 95% CI 0.008-0.58) in non-upgrading group. Logistic regression analysis demonstrated that triple aPL positivity was an independent factor for switching to a more effective therapy protocol (p <0.0001, OR 98, 95% CI 10.7-897.54). All eight switched patients achieved a live birth. Conclusion: Using adjusted LMWH doses and upgrading therapy at the first signs of pregnancy complications led to a high rate of live births in a relatively large group of APS patients. The study outlines the criteria for prescribing appropriate therapy for various subsets of these patients and for switching/upgrading the treatment protocol when it is no longer sufficient. Unfortunately, for the moment there are no evidence-based guidelines on the ideal additional treatment in refractory to conventional therapy APS patients. The present results will hopefully help point the direction of future clinical trials investigating the efficacy and safety of the different therapies on large numbers of APS pregnant patients in order to identify the benefits and limits of different treatment strategies administered from the beginning of pregnancy. Disclosure of Interests: Ariela Hoxha Speakers bureau: Celgene, UCB, Novartis, Sanofi, Werfen, Maria Favaro: None declared, Antonia Calligaro: None declared, Teresa Del Ross: None declared, Alessandra Teresa Ruffatti: None declared, Chiara Infantolino: None declared, Marta Tonello: None declared, Elena Mattia: None declared, Amelia Ruffatti: None declared